2021
DOI: 10.1111/tbed.14002
|View full text |Cite
|
Sign up to set email alerts
|

A deletion in SARS‐CoV‐2 ORF7 identified in COVID‐19 outbreak in Uruguay

Abstract: The analysis of genetic diversity in SARS‐CoV‐2 is the focus of several studies, providing insights into how the virus emerged and evolves. Most common changes in SARS‐CoV‐2 are single or point nucleotide substitutions; meanwhile, insertions and deletions (indels) have been identified as a less frequent source of viral genetic variability. Here, we report the emergence of a 12‐nucleotide deletion in ORF7a, resulting in a 4‐amino acid in‐frame deletion. The Δ12 variant was identified in viruses from patients of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 39 publications
0
28
0
Order By: Relevance
“…The deletions within the ORF7a and ORF7b region have also previously been reported [ 15 - 18 ]. ORF7a activates the nuclear factor kappa-light-chain-enhancer of activated B cells (NF-kappa B) pathway and induces proinflammatory cytokine expression [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 63%
“…The deletions within the ORF7a and ORF7b region have also previously been reported [ 15 - 18 ]. ORF7a activates the nuclear factor kappa-light-chain-enhancer of activated B cells (NF-kappa B) pathway and induces proinflammatory cytokine expression [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 63%
“…SARS-CoV-2 ORF7a is also linked to viral transmission and pathogenesis through inhibition of interferon signaling [ 13 , 14 ]. Several studies have reported deletions in the ORF7a gene in SARS-CoV-2 isolates, but were unable to place them in the clinical context [ 15 , 16 , 17 , 18 , 19 ]. However, in vitro deletion of ORF7a gene reduces replication of the synthetic virus [ 20 ], suggesting an important role of ORF7a in disease severity.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of drugs used for SARS-CoV-2 treatment are drugs currently in use for treatment of other diseases [243][244][245], and these have been evaluated for their efficacy using computational drug discovery analysis [246][247][248]. Although NGS has been used primarily for genome identification of SARS-CoV-2 [249][250][251][252], as well as for evaluation of mutations developed during viral spread in different countries [253][254][255], there are some studies wherein RNA sequencing is used for identifying new drug treatments. One such study has used NGS for evaluation of affected genes during SARS-CoV-2 infections.…”
Section: Ngs In Sars-cov-2 Drug Discoverymentioning
confidence: 99%